The determinants of corporate hedging decision and the impact of hedging strategies on firms' risk: evidence from Hong Kong and Chinese non-financial firms - WANG, FEIER (2017)
An increasing amount of corporations are using corporate risk management programs to control the risk exposure. Derivatives hedging activities are most common hedging instruments. The majority of prior researches focus on US and UK market. This paper employs a sample of 501 HK and Chinese non-financial firms over 2008 to 2016 to investigate on the determinants of corporate hedging decision and the purpose of HK and Chinese firms to use the financial derivative products. The hedging data of the sampled firms is manually collected from annual reports. Chinese firms show relatively lower portion in undertaking hedging products, since the state-ownership characteristic provides certain guarantee towards risk exposure. A combined approach of univariate and multivariate logistic regressions is employed to investigate on the determinants of hedging decision. The empirical results show that foreign risk exposure and firm size exhibit most significant positive relationship with both hedging and FX hedging decision. All the regression tests are iterated four times on groups involving a more comprehensive definition of hedging, in order to prevent biased non-hedgers and non FX-hedgers samples. The results support that the alternative definition of hedging is necessary to obtain more reliable and accurate conclusion. Finally, pooled OLS regression is used to distinguish the purpose of hedging activities. The test results imply that HK and Chinese non-financial firms use derivatives for hedging rather than speculation purpose.